Pharmacokinetics of an extended‐release formulation of eprinomectin in healthy adult alpacas and its use in alpacas confirmed with mange. Issue 2 (18th September 2016) - Pollock, J.; Bedenice, D.; Jennings, S. H.; Papich, M. G.
Abstract : The study objective was to determine the pharmacokinetics and clinical effects of an extended‐release 5% eprinomectin formulation (Longrange ® ) following subcutaneous (s.c.) injection in healthy ( n = 6) and mange‐infected ( n = 4) adult alpacas. High‐performance liquid chromatography was used to analyze plasma samples obtained at regular intervals for 161 days following a single 5 mg/kg injection s.c. in healthy alpacas, and for 5 days following each dose (3 treatments, 2 months apart) in mange‐affected animals. Skin scrapings and biopsies were performed pre‐ and post‐treatment at two comparable sites in alpacas with mange. Four alpacas served as healthy controls. Eprinomectin plasma concentrations showed a biphasic peak (CMAX ‐1: 5.72 ± 3.25 ng/mL; CMAX ‐2: 6.06 ± 2.47 ng/mL) in all animals at 3.88 ± 5.16 days and 77 ± 12.52 days, respectively. Eprinomectin plasma concentrations remained above 1.27 ± 0.96 ng/mL for up to 120 days. Hematocrit (35.8 vs. 31.3%, P < 0.003) and albumin (3.5 vs. 2.8 g/dL P < 0.006) reduced significantly over 6 months in multidose animals, while fecal egg counts did not differ between groups. Self‐limiting injection site reactions occurred in 9 of 10 animals. Pre‐ and post‐treatment skin biopsies showed reduced hyperkeratosis, but increased fibrosis, with 1 of 4 alpacas remaining positive on skin scraping for mange. In conclusion, alpacas require a higher eprinomectin dose (5.0 mg/kg s.c.) than cattle, to reach comparable plasma concentrations.